Salivary Gland Tumors-10 years’ experience at Peshawar Medical College - Malik, Mehreen (International Journal of Pathology, 2023)
Introduction: Salivary gland tumors (SGTs) are a rare disorder of diverse characteristics. Up to 13.5 people per lac population are affected by SGTs each year.Most of studies have shown geographic variation in the incidence and histopathologic types of salivary gland neoplasms. Objective: This study aimed to evaluate the salivary gland tumors for 10 years duration in patients’specimens received in Peshawar Medical College laboratory. Material and Methods: This study was conducted at Peshawar Medical College, Peshawar. In this epidemiological study, 100 medical records of patients with salivary gland neoplasms for 10 years duration (January 2011-December 2021) were reviewed.The clinical data and histopathological features were statistically analyzed using SPSS version 25. Results: Data showed Pleomorphic adenoma as the most prevalent benign Salivary gland tumor whereas adenoid cystic carcinoma ranked as the most common malignant Salivary Gland Tumor. Patients were between the age group 13-100 years. Among these 56 were males and 44 were female. Benign tumors were mainly found in the parotid gland while malignant tumors were more prevalent in minor salivary glands. Conclusion: Pleomorphic adenoma is the most common benign salivary gland tumor and adenoid cystic carcinoma was the most frequently observed malignant tumor. Although most of the results of this study were similar to those reported in other populations, some differences were observed.